Editorial Note: Special Issue: Law and Language - Angelo, Tony; Holmes, Janet; Stephens, Māmari (Victoria University of Wellington Law Review, 2011)
This special issue of the Victoria University of Wellington Law Review is a collaborative one with the Revue Juridique Polynesienne. The theme of the issue is "Law and Language", with the publication being something of a soundboard and a test of the local academic interest in such interdisciplinary studies. The issue covers a broad range of topics and contains articles in both French and English.